Evolving paradigms of aspen ecology and management: impacts of stand condition and fire severity on vegetation dynamics. Issue 1 (26th January 2015) - Krasnow, Kevin D.; Stephens, Scott L.
Abstract : Quaking aspen ( Populus tremuloides Michx.) comprises only a small fraction of western USA forests, yet contributes significant biological diversity and is considered by many to be the most important deciduous forest type in western North America. There is currently a high level of concern in the western United States as many seral aspen populations are declining in vigor due to drought, ungulate browsing, and lack of disturbance. It is also highly uncertain if aspen will successfully accommodate future climate warming via migration through seedling establishment, which has been assumed to be extremely rare. In recent years, fundamental assumptions concerning aspen clonal age, regeneration, and genetic diversity have been challenged, and these findings have important implications for management and persistence of aspen in western USA forests. In this study, we compared regeneration dynamics of aspen revitalization strategies (conifer removal and prescribed fire) to unplanned wildfires of low, moderate, and high severity in the Sierra Nevada, and related multiple components of pre‐fire stand composition to post‐fire aspen regeneration. To better understand the viability of aspen migration to accommodate future climate warming, we examined recent events of aspen seedling establishment. We found substantial evidence that greater disturbance severity yields increased aspen sprout density and growth rates, and that live conifer and/or dead aspen basal area in a stand before a fire reduces post fire sprout density. Additionally, we found evidence that aspen seedling establishment is more common than has been assumed, and represents a viable means for aspen migration. Future climate changes will present both challenges and opportunities for aspen. Increased temperatures and drought will stress existing populations, but increased high severity fire in forested areas, may provide opportunity for successful aspen migration and genet establishment. In addition to revitalizing existing aspen stands, future management goals should include the establishment of new stands in more suitable habitat.